Enhancing common‐mode suppression in microstrip differential lines by means of chirped and multi‐tuned electromagnetic bandgaps. Issue 2 (February 2016) - Vélez, P.; Valero, M.; Su, L.; Naqui, J.; Mata‐Contreras, J.; Bonache, J.; Martín, F.
ABSTRACT: This article presents common‐mode suppressed microstrip differential lines based on chirped electromagnetic bandgaps (EBGs). To achieve common‐mode suppression in a wide band, the common‐mode impedance is modulated following a sinusoidal chirping, whereas the differential‐mode impedance is kept unaltered, thus ensuring that the line is transparent for that mode. The result is a differential line exhibiting common‐mode suppression in a band from 2.45 GHz up to 7.37 GHz centered at 5 GHz (98.4% bandwidth). As compared to previous works, based on single tuned or double tuned EBGs, the proposed technique is useful to achieve wider rejection bands for the common mode. Nevertheless, the authors also propose an alternative based on multi‐tuned EBGs, in order to obtain a comparable fractional bandwidth. In both cases, the design procedure is simple, and the ground plane is kept unaltered. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:328–332, 2016